The BRICS in International Development
XXI, 248 p. 5 illus.
Keywords: This book offers a comprehensive comparative perspective on the increasingly significant development cooperation activities of the BRICS. Providing a powerful set of insights into the drivers for engagement within each country, it brings together leading experts from Brazil, Russia, India, China, South Africa and OECD countries. The authors review the empirical evidence for the BRICS’ modes of development cooperation and their geographical reach, and explore the historical background and patterns of international development engagement of each country. They also present a cutting-edge analysis of the broader geopolitical shifts, distinctive ideologies and normative discourses that are influencing and informing their engagement in increasingly ambitious joint projects such as the New Development Bank. This collection is essential reading for anyone seeking to understand the rapidly changing landscape of international development.